Technology enhanced learning for people with disabilities approaches and applications - Ordóñez de Pablos, Patricia 1975-; Zhao, Jingyuan 1968-; Tennyson, Robert D. (Information Science Reference, 2011)
"This book brings together academics, policy-makers and practitioners, with the goal of delivering a reference edition for all those interested in approaches and applications of technology enhanced learning for people with disabilities" - Provided by publisher
Includes bibliographical references
1. Benefits of CSCL for learners with disabilities / Robert Tennyson, Robert Jorczak -- 2. Computer interventions for children with disabilities / Robert Tennyson -- 3. China special education / Jingyuan Zhao -- 4. Learning applications for disabled people / Athanasios Drigas, Dimitris Kouremenos, John Vrettaros -- 5. A paradigm in transition / Pablo Albino, Fernando Gatica, Jos e Armend ariz-I nigo -- 6. Personal learning enviroments / Jaime Ribeiro ... [et al.] -- 7. Automatic speech recognition to enhance learning for disabled students / Pablo Revuelta ... [et al.] -- 8. School of the future / Michela Ott -- 9. Public information services for people with disabilities / Angel Garc ia-Crespo ... [et al.] -- 10. Elderly people with disabilities in the Internet age / Panagiotis Kyriazopoulos ... [et al.] -- 11. Supports for and barriers to implementing assistive technology in schools / Susanne Croasdaile ... [et al.] -- 12. Theory of mind in autistic children / Tariq Khan -- 13. M-learning / Saif alZahir -- 14. Applying virtual reality (VR) to the detection and treatment of clinical problems in educational settings / Jos e Carmona ... [et al.]
Keywords: Students with disabilities / Computer-assisted instruction; Computers and people with disabilities; Educational technology; Behinderung; Computerunterstützter Unterricht; Schüler; Aufsatzsammlung